Stratigraphic, Sedimentological and Faunal Evidence for the Occurrence of Pre-Sangamonian Artefacts in Northern Yukon - Jopling, A.V.; Irving, W.N.; Beebe, B.F. (ARCTIC, 1981)
The stratigraphic position of artefacts of undoubted Pleistocene age found in the Old Crow Basin has long been in question. We report on geological, palaeontological and archaeological excavations and studies there which show that artefacts made by humans occur in deposits of Glacial Lake Old Crow laid down before Sangamonian time, probably during a phase of the Illinoian (=Riss) glaciation. The geological events surrounding and following the deposition of Glacial Lake Old Crow were complicated by a changing lake level, localized soft-sediment flowage, pingo formation and dissolution, and by the colluvial transport of vertebrate fossils and artefacts. Following deepwater stages of the Lake, an environment not greatly different from that of the present is suggested by the excavated vertebrate fauna and by permafrost features, although warming during the succeeding Sangamon can be considered likely. Sangamonian and later phenomena in the Old Crow Basin are referred to briefly; they show that humans persisted in the area for some time.